2022
DOI: 10.1002/nbm.4706
|View full text |Cite
|
Sign up to set email alerts
|

γ‐aminobutyric acid measurement in the human brain at 7 T: Short echo‐time or Mescher–Garwood editing

Abstract: The purposes of the current study were to introduce a Mescher-Garwood (MEGA) semi-adiabatic spin-echo full-intensity localization (MEGA-sSPECIAL) sequence with macromolecule (MM) subtraction and to compare the test-retest reproducibility of γ-aminobutyric acid (GABA) measurements at 7 T using the sSPECIAL and MEGA-sSPECIAL sequences. The MEGA-sSPECIAL editing scheme using asymmetric adiabatic and highly selective Gaussian pulses was used to compare its GABA measurement reproducibility with that of short echo-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…E ects on GABA/creatine ratio Measuring GABA using 1 H-MRS is challenging due to the low concentration of GABA in the brain and the spectral overlap with other metabolites. Thus, GABA levels should be interpreted with caution, unless measured at higher magnetic field strength (≥7 T MRS) or special sequences (74). Even though we found a significant increase of GABA/creatine ratio in group IEU, the median relative CRLB were high, so the current results should be interpreted with care.…”
Section: E Ects On Glucose/creatine Ratiomentioning
confidence: 58%
“…E ects on GABA/creatine ratio Measuring GABA using 1 H-MRS is challenging due to the low concentration of GABA in the brain and the spectral overlap with other metabolites. Thus, GABA levels should be interpreted with caution, unless measured at higher magnetic field strength (≥7 T MRS) or special sequences (74). Even though we found a significant increase of GABA/creatine ratio in group IEU, the median relative CRLB were high, so the current results should be interpreted with care.…”
Section: E Ects On Glucose/creatine Ratiomentioning
confidence: 58%
“…Therefore, besides employing the editing method that facilitates the separation of GABA from other metabolites and achieves good measurement reproducibility, our study highlights the potential for achieving this goal by optimizing the basis‐set approach with the short‐TE method. The results revealed that, in mPFC, the CV of GABA using sSPECIAL combined with the LM approach can be reduced to a similar level compared with those provided by the MEGA‐sSPECIAL method 35 . Furthermore, the optimization of GABA spin parameters plays a crucial role in achieving accurate fitting and quantification.…”
Section: Discussionmentioning
confidence: 94%
“…The homogeneities of the static magnetic field were optimized with the FASTMAP shimming method 32,33 . The 1 H MR spectra were acquired using semi‐adiabatic spin‐echo full‐intensity‐acquired localization (sSPECIAL) 9 (TR/TE = 4000/16 ms, bandwidth = 4 kHz, 4096 datapoints) from the thalamus ( n = 3, 120 averages, voxel size = 20 × 18 × 16 mm 3 ), 34 the primary motor cortex (M1) ( n = 5, 128 averages, voxel size = 30 × 20 × 20 mm 3 ), and the mPFC ( n = 3, 128 averages, voxel size = 30 × 20 × 20 mm 3 ) 35 . The outer volume suppression was interleaved with VAPOR water suppression 36 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This limitation is partially due to the much lower GABA concentration in comparison with other brain metabolites and the GABA is obscured by signals from more abundant metabolites. Measurements at higher magnetic field strengths and dedicated sequences could help to overcome this technical issue ( 52 ).…”
Section: Discussionmentioning
confidence: 99%